Sustainable Remediation and Site Reuse - Eskes, Sander; Ryan, John (Águas Subterrâneas, 2011)
This presentation will provide an overview of the application of sustainable principles and tools to the cleanup and redevelopment of contaminated sites. This is an area of rapid development within the environmental profession, with new tools, business practices, and performance standards for identifying, evaluating, and managing the “collateral” impacts of cleanup and site development projects to the environment, economy and society coming from many organizations. A series of case studies will be presented which include: • Cleanup and redevelopment of a former refinery into a multi use wildlife refuge, kayak course, golf course and business park • Reuse of a former landfill for a 4 mega watt solar energy facility • Cleanup and reuse of a wood treating facility for an airport expansion • Use of wetlands for site remediation and public space